The role of work engagement in the relation between daily events and individuals’ well-being - Junça Silva, A.; Caetano, António; Lopes, M. (17th congress of the European Association of Work and Organizational Psychology, 2015)
In this study we aim to explore whether daily hassles and uplifts at work and work engagement can be considered as daily antecedents of well-being. We also intend to test if work engagement plays a mediating role in the relationship between daily hassles and uplifts and well-being on the daily level. To achieve this, we conducted two diary studies. Instudy 1, we explored this relationship on a sample of one hundred and eighty one part-time workers who answered a daily questionnaire for (at least) four days (N =181 × 4 = 724). The results of hierarchical linear modelling demonstrated that work engagement fully mediated the effects of daily uplifts on well-being and partially mediated the effects of daily hassles on well-being. In study 2, we extended the hypothesis to a sample of full-time employees. Fifty-one workers filled in a questionnaire at the end of each working day for ten consecutive days (N = 51 ×10 = 510). The results revealed that daily uplifts were positively associated with well-being. The effects of daily uplifts and hassles on well-being were fully mediated by work engagement. The relationships explored provide new theoretical elements for models that explain which variables influence employees’ well-being. The implications for employee health and organizational success are discussed.